Rancang Bangun Aplikasi Tes Psikologi Online Berbasis Web untuk Menunjang Keputusan Kelas Peminatan Siswa (Studi Kasus Biro Instrumentasi Bimbingan Konseling Empatik Mataram) - Riga Anggraini Putri; Moh. Ali Albar; Nadiyasari Agitha (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2020)
Decisions of specialization classes in high school students can be made based on the recommendations of the psychology test results. At SMAN 1 Selong in collaboration with a certified institution namely Biro Instrumentasi Bimbingan dan Konseling Empatik Mataram to execute the tests. In this case, the psychological test system is still manual, the manual system of psychological testing activities requires a lot of cost and time. The results of these psychological tests are analyzed manually by institutional experts to obtain results from specialization classes and require a long time. Based on these problems, an online psychology test application was designed and built to streamline time costs. Psychological test results are analyzed automatically using the weighted product method to get the results of recommendations accurately and quickly. The criteria used by the weighted product method to obtain student specialization class recommendations are 13 criteria consisting of sub-tests on psychological tests. The suitability between the results of expert recommendations and weighted product recommendations is 70%. System testing uses the method of BlackBox testing and Mean Opinion Score (MOS). The results of testing the BlackBox method on functions that exist on the system have valid conclusions or the system can run as expected. The results of testing using MOS with 30 respondents on average 4.4 categorized the system running well.